Carbamazepine Toxicity–Induced Spindle Coma: A Novel Case Report. Issue 2 (March 2017) - Chauhan, Bhumir; Patanvadiya, Amitkumar; Dash, Gopal Krishna
Abstract : Abstract: A 9-year-old girl presented with alleged history of deliberate ingestion of 4 g of carbamazepine, following which she became comatose. A bedside electroencephalogram (EEG) was performed to rule out nonconvulsive status epilepticus, which showed presence of spindle coma (SC), not reactive to noxious stimuli. Following hemodialysis, a second EEG showed absence of SC and complete clinical recovery. We present this unique case of carbamazepine-induced SC, thereby highlighting the extent of the etiologic spectrum of SC and discussing the literature related to this association.